The Effect of Chilli Extract on Gastroprotective Function in Male - Tahyatul Bariroh; Siska Siska (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Chilli is one of plant from genus Capsicum and as vegetable commodities most consumed by the Indonesian people. Chilli contains a unique compound called capsaicin which gives a burning sensation like burning when consumed. This research aims to determine the effect of chilli extract on gastroprotection in the stomach of mice. The study used 35 white male rats were divided into seven groups, one group as the control group, and six groups were given extracts from three varieties of chilli (red chilli, green chilli, and chilli) with high doses (1 g / kg bb) and low doses (0.5 g / kg bb) for 14 days. On the 15th day, gastric decapitation and isolation were carried out to make histological preparations of the rat's stomach. The results showed mucosal tissue in the stomach of rats given a dose of 0.5 g/kg BW remained in normal condition compared to the group of rats given high doses of chilli. In this group, a lot of damage to the gastric mucosal tissue of rats (ulcers). This study concludes that consuming 0.5 g/kg BW chilli does not cause damage to the gastric mucosal tissue of rats.Keywords: Chilli, Gastric mucose, Gastroprotective